FILSAFAT MOHAMMAD ABID AL JABIRI DAN RELEVANSINYA DALAM PEMIKIRAN ISLAM KONTEMPORER - Firdausy, M. Anwar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
Some ideologies of philosophy thinking, such as Rationalism, Empirism, and Positivism which were born in western countries could not be accepted easily in the Muslim countries many years ago. However, the awareness for not to refuse the mindset or western epistemology, finally could be tolerated by the Muslim scholars, such as Muhammad Abid aljabiri who strived to introduce his new theory of Bayani, Burhani, and Irfani. Those three theories are not substantially different from western epistemology. With different rhetoric, aljabiri strived to make his theories became a bridge to the contemporary Islamic thinking. The source of the Bayani thinking theory is from texts or messages from God, while the Burhani thinking theory is from the reality of nature, humanities and religion. Meanwhile, the theory of Irfani thinking is from the experience of the deepest soul or it is called reflective in the term of Isyroqi tradition. In addition, the theories are also as a reflection of his sadness toward the bad reality of the disability of the Arabian people to follow modem civilization.